Reinventing African Higher Education - (:unkn) unknown (My University, 2024)
COVID-19 has disrupted traditional teaching and learning methods. In response to school closures, nearly 220 million higher education students worldwide lost physical access to campuses (UNESCO, 2022, p. 8). Consequently, institutions were forced to transition to new teaching modalities.Moreover, higher education today consists of learners from Generation Z, characterized by their use of information and communication technologies (Bassiouni & Hackley, 2014, p. 116). With such learners, teaching and learning methods must be rethought "to better meet the needs of these new profiles" (Abgrall et al., 2022, p. 2). This presents a challenge for universities to engage students in learning environments that enable them to thrive in a digital world and a rapidly evolving professional context.As a result, pedagogical engineers have become the architects of this transformation in higher education.
Keywords: African Research